A photographic atlas of the human body : with selected cat, sheep,and cow dissections. - Tortora, Gerard J. (Menlo Park, 2000)
This book is about: Orientation to the human body; Tissues; The skeletal system; Articulations; The muscular system; The cardiovascular system; ...